2011
DOI: 10.1111/j.1600-0706.2011.19849.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the outcome of plant–granivore interactions

Abstract: In many interspecific interactions, the balance of costs and benefits varies with ecological circumstances. As a prominent example, seed‐caching granivores may act as seed predators and reduce plant recruitment or as seed dispersers and increase recruitment, making it difficult to interpret whether differences in seed removal by granivores would harm or benefit plant populations. We used a heuristic model to evaluate the outcome of plant‐granivore interactions, using commonly measured field data: probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 54 publications
2
115
2
Order By: Relevance
“…They can influence tree recruitment through selective foraging on seeds (García et al 2005;Zwolak et al 2010) and seedlings (Ostfeld et al 1997;Gómez et al 2003). On the other hand, many species of rodents promote forest regeneration by dispersing seeds and caching them in safe sites (den Ouden et al 2005;Zwolak and Crone 2012). Small mammals also eat and disperse spores of mycorrhizal fungi, thus enhancing functioning of forest trees (Schickmann et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They can influence tree recruitment through selective foraging on seeds (García et al 2005;Zwolak et al 2010) and seedlings (Ostfeld et al 1997;Gómez et al 2003). On the other hand, many species of rodents promote forest regeneration by dispersing seeds and caching them in safe sites (den Ouden et al 2005;Zwolak and Crone 2012). Small mammals also eat and disperse spores of mycorrhizal fungi, thus enhancing functioning of forest trees (Schickmann et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vander Wall 1990 and literature cited therein; Norconk et al 1998). Propagules overlooked by the hoarder, and which can also escape detection by other animals, can germinate successfully (Vander Wall 1990Zwolak and Crone 2011;Lenda et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Field evidence has shown that the survival or dispersal of individual seeds can change dramatically over a short timescale for a given plant population (Vander Wall 2002, Jansen et al 2004, Klinger and Rejmánek 2010, Xiao et al 2013). This may be the key point for many researchers to argue that the mutualism between scatterhoarders and plants is contextdependent (Theimer 2005, Klinger and Rejmánek 2010, Zwolak and Crone 2012. In summary, we propose three models to quantify the costs and benefits to a plant in relation to scatterhoarding animals that act as seed predators and seed dispersers.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, plant populations cannot be sustained and would go extinct (Latta 2010). There are few measurements of whether recruitment in plants benefits from seed dispersal via scatterhoarding animals (Jansen and Forget 2001, Theimer 2005, Zwolak and Crone 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation